A Path toward SARS-CoV-2 Attenuation: Metabolic Pressure on CTP Synthesis Rules the Virus Evolution. (30th October 2020) - Ou, Zhihua; Ouzounis, Christos; Wang, Daxi; Sun, Wanying; Li, Junhua; Chen, Weijun; Marlière, Philippe; Danchin, Antoine
Abstract: In the context of the COVID-19 pandemic, we describe here the singular metabolic background that constrains enveloped RNA viruses to evolve toward likely attenuation in the long term, possibly after a step of increased pathogenicity. Cytidine triphosphate (CTP) is at the crossroad of the processes allowing SARS-CoV-2 to multiply, because CTP is in demand for four essential metabolic steps. It is a building block of the virus genome, it is required for synthesis of the cytosine-based liponucleotide precursors of the viral envelope, it is a critical building block of the host transfer RNAs synthesis and it is required for synthesis of dolichol-phosphate, a precursor of viral protein glycosylation. The CCA 3′-end of all the transfer RNAs required to translate the RNA genome and further transcripts into the proteins used to build active virus copies is not coded in the human genome. It must be synthesized de novo from CTP and ATP. Furthermore, intermediary metabolism is built on compulsory steps of synthesis and salvage of cytosine-based metabolites via uridine triphosphate that keep limiting CTP availability. As a consequence, accidental replication errors tend to replace cytosine by uracil in the genome, unless recombination events allow the sequence to return to its ancestral sequences. We document some of the consequences of this situation in the function of viral proteins. This unique metabolic setup allowed us to highlight and provide a raison d'être to viperin, an enzyme of innate antiviral immunity, which synthesizes 3ʹ-deoxy-3′, 4ʹ-didehydro-CTP as an extremely efficient antiviral nucleotide.